#DiabetesOnAPlate: the everyday deployment and contestation of diabetes stigma in an online setting. Issue 2 (15th March 2023) - Blackwood, Leda; Gavin, Jeff; Arnott, Emma; Barnett, Julie; Dack, Charlotte; Johansen, Jessica
ABSTRACT: People living with Type 1 and Type 2 diabetes (T1DM &T2DM) report that media – including journalism, health promotion, and popular culture – are a primary source of stigmatic representations of diabetes, and that this compromises their physical and mental health. This view of diabetes as stigmatised is not shared by many health professionals and nor the wider public. We used an existing representation of diabetes on Instagram, #DiabetesOnAPlate, to examine how stigmatic representations of diabetes are (re)produced, discussed, and contested. Our analysis found that, consistent with the notion of diabetes as stigmatised, use of the hashtag #DiabetesOnAPlate on Instagram is associated with public health discourses of indulgent eating and with posts that signal recognition of this as a moral transgression. A subsequent on-line survey found that participants who did not have diabetes did not recognise a prototypical #DiabetesOnAPlate post as stigmatic. Whilst some with T1DM and T2DM did perceive and contest the stigma, T1DM participants did so for their group (but not for T2DM); and there was evidence that some T2DM participants internalised the stigma. These findings support concerns about the everyday, divisive nature of stigmatic representations of diabetes on social network sites, which on the one hand reflect public health discourse and on the other may compromise health policy objectives and exacerbate health inequalities.